Hipertextualidade e tradução intersemiótica: um mergulho nos mares da canção de Fernando Ribeiro e Arnaldo Sisson - Hévelyn Costa da Silva (2017)
This work proposes the construction of musical reinterpretations by taking the approach of popular song as an intersemiotic translation process, of Peirce's root, and as a hypertext construction based on the definition of hypertextuality proposed by Gérard Genette. The paper considers that such analysis proposal of song can inform the singer in the task of directing the development of musical arrangements in collaboration with other musicians/arrangers. In this context, I have chosen three songs of Em mar aberto's LP, by the singer-songwriter Fernando Ribeiro, as objects of study. which are: Não demora, Em mar aberto and Delírio. The theory of intersemiotic translation allowed me to consider the iconographic aspects of the album cover in dialogue with the songs. I then sought to identify how it exposes the relationship between the recording and supporting material; namely the verbal, aural and visual languages. On the other hand, the idea of hypertextuality led me to consider possible allusions, evocations and connections of that phonograph record with different types of works. In the perception of such links from one language to another, from one text to another, might lie a source capable of providing the singer creative resources for new interpretations. Thus, I believe, by interpreting the implicit meaning of the popular song the singer [now also a translator] would be able to guide other instrumentalists in the process of musical arrangement, the essense of this new of the song, always in connection to the original work, but without discarding their own perpectives as an interpreter and individual.